2009
DOI: 10.5694/j.1326-5377.2009.tb02929.x
|View full text |Cite
|
Sign up to set email alerts
|

Complications of otitis media in Indigenous and non‐Indigenous children

Abstract: In Australia, three to five children die each year because of otitis media complications, and 15 children will suffer permanent hearing loss each year as a result of otitis media. Extracranial complications occur most commonly, and include mastoiditis, cholesteatoma and otitis media with perforation. Intracranial complications are less common, and include meningitis, brain abscess and lateral sinus thrombosis. In Australia, approximately 60% of extracranial and intracranial complications of otitis media occur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 22 publications
1
51
0
6
Order By: Relevance
“…Our prevalence of ear infection was 7.9% among children aged 4 to 5 years and 3.3% among children aged 10 to 11 years. Incidence and prevalence rate of ear infections varied depending on age groups (highest in the first three years); however, differences in definitions and diagnostic measures make comparisons between studies very difficult [16, 18, 28]. For example, a US study of children aged 1–8 years using weekly otoscopy reported prevalence ranging from 7–30% for children aged 5 years and above.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our prevalence of ear infection was 7.9% among children aged 4 to 5 years and 3.3% among children aged 10 to 11 years. Incidence and prevalence rate of ear infections varied depending on age groups (highest in the first three years); however, differences in definitions and diagnostic measures make comparisons between studies very difficult [16, 18, 28]. For example, a US study of children aged 1–8 years using weekly otoscopy reported prevalence ranging from 7–30% for children aged 5 years and above.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of ear infection, whereby Australian indigenous children had at least an episode in the first year of life, is among the highest in the world and has resulted in a wide range of complications [16, 17]. According to data from Aboriginal Medical Service, rural and remote practitioners manage a greater caring burden than their urban counterparts; hence, affected children have less access to specialist ear health services and longer waiting times [18].…”
Section: Introductionmentioning
confidence: 99%
“…Australian Aboriginal children experience an excessive burden of otitis media (OM) and associated hearing loss, which causes difficulties in language acquisition and learning and has long-term effects on their life course (13). While 10 to 20% of nonindigenous children develop chronic or recurrent OM, the condition is almost universal among Australian Aboriginal children by 12 months of age and persists to school age (46).…”
Section: Introductionmentioning
confidence: 99%
“…The disproportionately high prevalence of middle ear disease and its complications in Aboriginal children can lead to disabling chronic ear disease, hearing impairment and negatively affect education, social circumstances and quality of life [10,11]. In 2004–05, rates of middle ear disease were four times as high among Aboriginal children aged 0–14 years as non-Aboriginal children in the same age group [3].…”
Section: Introductionmentioning
confidence: 99%